Exploring the factors affecting sponsored search ad performance. Issue 5 (29th July 2014) - Gupta, Agam; Mateen, Arqum
Abstract : Purpose: – The purpose of this paper is to conceptualize a model for sponsored search advertising by incorporating a number of factors which affect the performance of these ads. Design/methodology/approach: – The authors draw upon the professional experience and practitioner as well as academic literature to build and analyze the model. Propositions have been forwarded to delineate the various relationships at work in a sponsored search process. Findings: – The extant literature on this topic has so far been unable to provide a holistic overview. The paper offers propositions for explaining the role of various factors like the ad rank, branding, role of ad extensions and how impact of these factors may be sensitive to the device used for search. Practical implications: – This work is derived primarily from practice. It is hope that after due empirical validation, advertisers, users as well as search engines will benefit from this stream of research. Originality/value: – This is one of the first works to analyze a sponsored search ad at a micro level. It brings into focus one of the largely unexplored facets of sponsored search advertising.